Did Goliath have an eyesight defect or not? - Peterca, Vladimir (Sacra scripta, 2004)
Young David before the mighty Goliath represents one of the most interesting and fascinating pages that has deeply preoccupied the people of the Bible. This impressive story, apart from the historical fact purified of all its mythological elements, has a charm of its own, preserving the pattern common to all biblical narratives: God chooses the young and the helpless to manifest his glory and fullfil his plans. We can say that the whole biblical narrative about David and Goliath is set at the border between history and legend. David’s skillfullness constitutes the unexpected element of this biblical page. Goliath, fully armed, had no time for self-defence. David’s blow was fatal and uncommonly efficient. He had come to fight “in the name of the Lord” (1 Sam 17,45), while Goliath was destroyed by his own boastfullness, by the vanity and conceit with which he had constantly regarded the God of Israel. The biblical narrative underlines the dramatical manner of the Philistine domination. There was no hope left for Israel. The whole biblical material is the result of juxtaposing two different textual traditions, difficult in themselves to distinguish. This becomes obvious even from the fact that David is presented consequently as the young shepherd feeding his father’s sheep, and then in the service of King Saul at his court. From the very beginning, we expect an unfair struggle between the two. This was meant to put an end to the war between the two armies and settle the victory. All this is referred to in verses 40 – 54, which describe the simple but efficient weapons that David was possessing: - a shepherd’s staff; - five smooth stones from the stream; - a shepherd’s bag on his shoulders; - a catapult in his hand. This was David’s armour with which, up to that moment he had hunted the lions and bears which happened to attack his sheep. These were the weapons with which he intended now to face the Philistine. Goliath on the contrary armed to his teeth was looking forward to fighting with young David. And this was exactly what David was relying on. He knew that Goliath had certain problems with his eyesight. An article issued several years ago in the well-known West-German newspaper “Frankfurter Allgemeine Zeitung” was informing its readers about the way in which David managed to defeat Goliath. This should not surprise anyone, because the ancient Greek mythology contained similar giants, named Cyclops (in Greek: kukloy), who had only one eye usually set in the centre of their forehead. Therefore, young David would have rapidly defeated Goliath, leaving no uncertainties about his victory (cf. 1Sam 17,1 – 58). Young David would have known this failing of Goliath’s and consequently attacked him directly. Thus, we can explain the quick victory of David’s, who in spite of being armed only with a catapult and several river pebbles managed to defeat the mighty Goliath.